Informacinėmis ir komunikacinėmis technologijomis papildytų edukacinių aplinkų kaita - Brazdeikis, Vaino (Information & Media, 2009)
Šiandien edukacinės aplinkos sparčiai keičiasi. Tam didelę įtaką daro informacinių ir komunikacinių technologijų plėtra. Straipsnio tikslas – apžvelgti edukacinių aplinkų kaitos, susijusios su technologijų plėtra, ypatumus kintant pedagoginei paradigmai. Kaip mokslinio darbo rezultatas parengtas teorinis informacinėmis ir komunikacinėmis technologijomis papildytų edukacinių aplinkų kaitos modelis. Naudojant SITES2006 tyrimų duomenis įvertinta Lietuvos bendrojo lavinimo mokyklos edukacinė aplinka ir jos kaitą lemiantys veiksniai.Change of Educational Environments, Enriched with Information and Communication TechnologiesVaino BrazdeikisSummaryEducational environment is changing rapidly. Information and communication technology (hereinafter – ICT) are doing a large infl uence in it. The goal of the article is to analyze change of educational environment enriched with ICT in context of the change of the pedagogical paradigm. The conclusion was made: the educational environments enriched by ICT are a dynamic, new quality–oriented education teaching and learning spaces, which created and managed of the ICT competences’ teachers and where used ICT – based methods and tools are. As a result of scientifi c work prepared the four stage model of change of educational environments, enriched by ICT. In the model each stage are characterized by teacher competence, teaching method and infrastructure. Secondary analyze of data from SITES2006 research, allowed to make issue on educational environment in Lithuanian school. Analysis shows that the implementation of ICT in Lithuania schools meets in second (application) stage. Discussion on development of educational environments, enriched by ICT is proposed to achieve a balance between the various ongoing processes on infrastructure solutions and the teaching of ICT competence development and on updating learning objectives, content and methods.18px;">